The fuzzy TOPSIS method and its implementation in the R programme - Dudek, Andrzej; Jefmański, Bartłomiej (Business Informatics, 2015)
The TOPSIS method (Technique for Order Preference by Similarity Ideal Solu-tion) suggested by Hwang and Yoon [1981], belongs to the group of pattern linear ordering methods of multidimensional objects. A characteristic feature of this method is a way to evaluate a synthetic criterion’s values, which takes into consideration the distance of an evaluated object from a positive-ideal solution as well as from a negative-ideal solution. The fuzzy TOPSIS method enables the linear ordering of objects described through linguistic variables, whose values are expressed in the form of triangular fuzzy numbers. In this arti-cle, a way of synthetic measurement estimation in environment R was presented, according to the assumptions of the fuzzy TOPSIS method proposed by Chen [2000]. Scripts, which are included in the article make the accomplishment of this particular method’s stages possible
Informatyka Ekonomiczna = Business Informatics, 2015, Nr 1 (35), s. 19-27
Keywords: linear ordering; fuzzy TOPSIS; fuzzy number; linguistic variable; R programme; porządkowanie liniowe; rozmyta metoda TOPSIS; liczby rozmyte; rozmyte wagi; modele IRT